Probable transfusion-transmitted Zika virus in Brazil - Barjas-Castro, Maria L.; Angerami, Rodrigo N.; Cunha, Mariana S.; Suzuki, Akemi; Nogueira, Juliana S.; Rocco, Iray M.; Maeda, Adriana Y.; Vasami, Fernanda G.S.; Katz, Gizelda; Boin, Ilka F.S.F.; Stucchi, Raquel S.B.; Resende, Mariângela R.; et al. (Wiley, 2016)
BACKGROUND: Zika virus (ZIKV) is an emerging arthropod-borne flavivirus transmitted by Aedes mosquitoes. Recent commentaries regarding ZIKV routes of transmission describe a potential transmission by transfusion. Herein, we report a probable case of transfusion-transmitted ZIKV infection through a platelet transfusion that was detected from postdonation information. CASE REPORT: A blood donor made a voluntary telephone report to the blood donor facility 3 days after donation and informed the facility of a febrile illness (fever, malaise, and headaches). Due to the ongoing dengue epidemic, the initial clinical investigation included dengue among other possible diagnoses. The serology and molecular laboratory results excluded dengue infection. However, stored samples from the donation were positive for ZIKV on reverse transcription-polymerase chain reaction (RT-PCR) analysis. A retrospective investigation demonstrated that the platelet concentrate, which was part of a pool, had been transfused after a liver transplantation. A physician had evaluated the patient 4 days after surgery. Laboratory investigation showed enzyme-linked immunosorbent assay results that were negative for dengue immunoglobulin M antibodies; however, the results were positive for hemagglutination inhibition antibodies against flavivirus. ZIKV RT-PCR and virus isolation analyses in cell cultures from recipient serum were both positive. The sequencing confirmed ZIKV in the donor and patient samples. Ten partial nucleotide sequences from the ZIKV strain that were detected in the donor were aligned and compared with the ZIKV genome detected in the recipient, revealing a 99.8% homology between the two strains. CONCLUSIONS: This is a case of probable transmission of ZIKV through blood transfusion. The patient had been transfused with the blood product from an infected donor, most likely in the incubation period after ZIKV infection but prior to clinical disease onset. This report emphasizes the importance of postdonation information and recipient investigations during outbreaks of potentially blood-borne infections.